Penerapan Standar Akuntansi Pemerintah (SAP) Untuk Meningkatkan Efektivitas Penganggaran Di Kementerian - Tia Fahda Absyari; Sonny Fransisco Siboro; Maulida Hasanah; Rianyta Tanjung (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The Indonesian government executes Government Bookkeeping Measures (SAP) to extend straightforwardness and responsibility in state financial management. One of the most goals of actualizing SAP is to extend the adequacy of budgeting in ministries. Executing SAP in government bookkeeping benchmarks is an imperative step to extend the viability of budgeting in services. This consider or extend centers on actualizing SAP to disentangle the budgeting prepare within the service. This may include joining arranged costs with the budget, overseeing the budget in different ways, and utilizing SAP highlights such as the budget discharge work.